Evaluation of somatosensory cortical processing in extremely preterm infants at term with MEG and EEG. Issue 2 (February 2015) - Nevalainen, Päivi; Rahkonen, Petri; Pihko, Elina; Lano, Aulikki; Vanhatalo, Sampsa; Andersson, Sture; Autti, Taina; Valanne, Leena; Metsäranta, Marjo; Lauronen, Leena
Highlights Secondary somatosensory cortex (SII) responses complement neonatal neurological evaluation in predicting neurodevelopmental outcome in extremely preterm infants. SII responses can be measured with MEG as well as with the routinely available bedside EEG-SEP recordings. Use of sensory responses as a part of routine EEG studies holds promise to significantly expand early neurophysiological evaluation of neonates after adversities.